2016
DOI: 10.1002/bem.21965
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed sleep in individuals with idiopathic environmental intolerance attributed to electromagnetic fields (IEI‐EMF): Melatonin assessment as a biological marker

Abstract: Individuals who suffer from idiopathic environmental intolerance attributed to electromagnetic fields (IEI‐EMF) complain of a variety of adverse health effects. Troubled sleep remains a recurrent and common symptom in IEI‐EMF individuals. Melatonin, a circadian hormone, plays a major role in the sleep process. In this study, we compared levels of melatonin between a sensitive group (IEI‐EMF, n = 30) and a non‐sensitive control group (non IEI‐EMF, n = 25) without exposure to electromagnetic sources. Three quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…The strongly impaired subjective sleep quality of our participants might also be caused by biopsychosocial factors that are unrelated to EMF exposure. Although disturbances in sleep quality belong to the most frequent complaints related to IEI-EMF (R€ o€ osli et al, 2004), most of the studies have not found an association between impaired sleep quality and actual EMF exposure (Andrianome et al, 2016;Mohler et al, 2010Mohler et al, , 2012. Nevertheless, subjective quality of sleep has been associated with poor self-rated health, low level of social support and perceived stress in previous studies, while objective sleep efficiency was unrelated to subjective sleep quality, psychosocial characteristics or affect (Jackowska et al, 2011;Tworoger et al, 2005).…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…The strongly impaired subjective sleep quality of our participants might also be caused by biopsychosocial factors that are unrelated to EMF exposure. Although disturbances in sleep quality belong to the most frequent complaints related to IEI-EMF (R€ o€ osli et al, 2004), most of the studies have not found an association between impaired sleep quality and actual EMF exposure (Andrianome et al, 2016;Mohler et al, 2010Mohler et al, , 2012. Nevertheless, subjective quality of sleep has been associated with poor self-rated health, low level of social support and perceived stress in previous studies, while objective sleep efficiency was unrelated to subjective sleep quality, psychosocial characteristics or affect (Jackowska et al, 2011;Tworoger et al, 2005).…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Concurrently, some individuals, such as electrohypersensitive (EHS) individuals complain of sleep disturbances or other symptoms when they are exposed to EMF [Andrianome et al, 2018], and melatonin was suspected to be disturbed in this population, therefore causing sleep disturbances; but a recent study did not confirm this hypothesis [Andrianome et al, 2016].…”
Section: Rationale For Studying Melatonin and Cortisolmentioning
confidence: 99%
“…Melatonin is produced by the pineal gland in a circadian rhythm with peak levels observed at night in human beings (13,14). It is closely related to sleep and is generally considered a clock rhythm biomarker (15)(16)(17). Compare with other visible light, blue light is the most effective for melatonin inhibition and could reset melatonin circadian rhythm (15).…”
Section: Introductionmentioning
confidence: 99%